THE CONTRADICTIONS OF WORSHIP IN THE PARISH CHURCH OF TARAPACÁ (1880 - 1897). ARTICULATING THE DEVOTION - Figueroa, Carolina (Revista de Historia Social y de las Mentalidades, 2025)
The aim of this work is to analyze the establishment of the Chilean ecclesiastic adminstration at the San Lorenzo de Tarapacá parish between 1880 and 1897. The labor of the first chilean priests is highlighted, presenting the relationship that they had with the Andean communities and emphasizing frictions in the worship articulation.
Keywords: Ecclesiastic Adminstration; Objects of Worship; Andean Community; Religious Syncretism